Academic resilience as mediator of multidimensional perfectionism and academic performance among gen-Z undergraduate students - Owen Ze Hua Choo; Kususanto Ditto Prihadi (Institute of Advanced Engineering and Science, 2019)
This study focused on the relationship of two dimensions of perfectionism (perfectionistic strivings, and perfectionistic concerns) and academic performance, with the role of academic resilience as mediator. Participants including 132 undergraduate students form age range 18 to 25, from first year to fifth year in their studies mainly from a Malaysian psychology undergraduate program were asked to fill questionnaires containing measures for perfectionism, academic resilience and academic performance. Although only partial mediations occurred, both hypotheses where academic resilience would mediate relationships between both dimensions of perfectionism and academic performance were supported. Findings suggested that other variables aside academic resilience could have played a role in predicting perfectionist’s academic performance. Findings also suggested interplay of academic performance acting as both protective factor and outcome of academic resilience.